2023
DOI: 10.3390/s23063359
|View full text |Cite
|
Sign up to set email alerts
|

Photoplethysmography Driven Hypertension Identification: A Pilot Study

Abstract: To prevent and diagnose hypertension early, there has been a growing demand to identify its states that align with patients. This pilot study aims to research how a non-invasive method using photoplethysmographic (PPG) signals works together with deep learning algorithms. A portable PPG acquisition device (Max30101 photonic sensor) was utilized to (1) capture PPG signals and (2) wirelessly transmit data sets. In contrast to traditional feature engineering machine learning classification schemes, this study pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These studies all involved the rehabilitation assessment of stroke. In the first study [26], Wei et al's model (CNN-LSTM-Attention) achieved only 72.73% accuracy. In the second study [17], based on the NIHSS scale, 234 features were extracted from EKG, ABP, and PPG signals, and a linear kernel SVM classifier was employed, resulting in an accuracy of 82.7%.…”
Section: Multi-modality Approachmentioning
confidence: 98%
See 1 more Smart Citation
“…These studies all involved the rehabilitation assessment of stroke. In the first study [26], Wei et al's model (CNN-LSTM-Attention) achieved only 72.73% accuracy. In the second study [17], based on the NIHSS scale, 234 features were extracted from EKG, ABP, and PPG signals, and a linear kernel SVM classifier was employed, resulting in an accuracy of 82.7%.…”
Section: Multi-modality Approachmentioning
confidence: 98%
“…In previous research, Wei et al [26] designed a PPG acquisition device and proposed a model that combines the Convolutional Neural Network (CNN), Long Short-Term Memory (LSTM), and an attention mechanism This model achieved a good accuracy rate of 99.1% in the diagnosis and identification of hypertension. However, when using this model for stroke-patient rehabilitation assessment, the accuracy rate was found to be relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, recently published papers are related to weather PPG wave patterns to calculate blood pressure. Yan et al 35 reported a PPG method that can work with a degree-learning algorithm, which is beneficial for the diagnosis and identification of hypertension. Liang et al 36 reported an approach to hypertension management based on arterial wave propagation theory and investigated changes in different BP levels.…”
mentioning
confidence: 99%